Nanoparticles generation using monodisperse droplets by an ultrasonic transducer. Issue 7 (27th May 2020) - Fujimoto, Nozomu; Kanda, Takefumi; Katsuta, Masaya; Sakata, Yusaku; Yamada, Yoshiaki; Seno, Norihisa; Nakazaki, Yoshiaki; Otoyama, Takafumi
Abstract: In recent years, a production of nanoparticles has been required in many fields such as production process for electronic materials, foods, and medicine. By using recrystallization process, nanoparticles can be formed by quenching a solution. We have generated monodisperse droplets by using an ultrasonic torsional transducer and a micropore plate to form fine nanoparticles by quenching droplets. In this nanoparticle production system, formed nanoparticles have a diameter of 79.9 nm when the applied voltage for the transducer and the diameter of micropore to generated micro droplets were 100 Vp‐p and 50 μm. We have successfully obtained fine nanoparticles from monodisperse droplets generated by using the ultrasonic torsional transducer. This result shows that the proposed system is effective for the miniaturization of the alum particles.